Stigma and Minority Stress as Social Determinants of Health Among Lesbian, Gay, Bisexual, and Transgender Youth: Research Evidence and Clinical Implications - Hatzenbuehler, Mark L; Pachankis, John E (The Pediatric clinics of North America, 2016)
In this article, we review theory and evidence on stigma and minority stress as social/structural determinants of health among lesbian, gay, bisexual, and transgender (LGBT) youth. We discuss different forms of stigma at individual (eg, identity concealment), interpersonal (eg, victimization), and structural (eg, laws and social norms) levels, as well as the mechanisms linking stigma to adverse health outcomes among LGBT youth. Finally, we discuss clinical (eg, cognitive behavioral therapy) and public health (eg, antibullying policies) interventions that effectively target stigma-inducing mechanisms to improve the health of LGBT youth.